Tempus sacratus : notas acerca do cinema de Andrei Tarkovski - Bastos, Mariana do Nascimento da Silva (2021)
The present study consists of a reflexive elaboration on the oeuvre and theory of Russian filmmaker Andrei Tarkovsky. We will, at first, go through some analysis and philosophical thesis on the concepts of sacredness and time, in order to shape a theoretical foundation and a possible «revelation» that we believe to be revealed through art and the authentic aesthetic experience. This experience, as referred to by Tarkovsky, constitutes a sensible mediation and a legitimate revelation of the creative spirit of man, as well as of its «state of creature», from the expanded field of theology. The dedication to the construction of a temporal sculpture is constituent of the film image of this director and has memory as its original matter. Memory, this time-immanent substance that unveils the human experience, will, in Tarkovsky manifest itself in a tone of historical criticism of the desacralization that occurred in modernity, and, sometimes, as a reflection of his affections. These are ideas that, above all in the analysis of certain titles in his filmography, will come to light and in them, we will seek to understand this poetic mediation that is founded on a notion and an experience of sacred time, which we believe was felt by the director. This notion implies a scission in man's own history and maintains an intimate relationship with a certain mysticism that surrounds and characterizes the work of Andrei Tarkovsky. Thus, as shadow and final praise, a «sublime suspension» before the aesthetic experience will occur, a suspension that happens outside of chronological (profane) time, in contact with what is said to be transcendent and sacred, and this experience is what emerges and fascinates us at the encounter with the Tarkovskian work.